Shahr-Tepeh and Toghei – Two Early Parthian Cities in Northeastern Iran - Mousavinia, Mehdi; Nami, Hassan (Anabasis. Studia Classica et Orientalia, 2019)
Northeast Iran is the home of many of the Early Parthian historical events, and one of the important parts of this region is Dargaz County. Located on the modern border of Iran and Turkmenistan, Dargaz is one of the areas related to the Parthian homeland, and here 85 archaeological sites of the Parthian period have been identified as a result of field surface surveys. Two of these sites, Shahr-Tepeh and Toghei, were probably Parthian urban centers. This article attempts to describe and evaluate the archaeological significance of the early Parthian urban centers in the Dargaz region using a descriptive-analytical approach and references to recent archaeological data. The present study argues that Shahr-Tepeh (c. 70 ha) and Toghei (c. 48 ha) were two significant urban centers in the early Parthian period. The proximity of Dargaz to Turkmenistan and its early Parthian settlements suggests that the three early Parthian period cities of New Nisa, Shahr-Tepeh and Toghei should be studied in one unified historical and geographical framework, a suggestion that could be supported by the similarity of the cultural material yielded by archaeological excavations at Nisa and Shahr-Tepeh, including pottery types and painted bricks.